A Taxonomic Study of Family Hemiramphidae from Indian Waters - Anwesha Behera; Jeevan T. M; A. Pavan Kumar; A. K. Jaiswar (Journal of Indian Fisheries Association, 2023)
The order Beloniformes consists of minor pelagic fish species that are considered valuable resources and can befound in marine, brackish, and freshwater habitats. In India, although they do not contribute significantly tocommercial fish landings, they play a remarkable role in the pelagic fishery of Tamil Nadu state, accounting forapproximately 42.6% of the total beloniform catch in the country. During this study, taxonomic analysis wasconducted based on morpho-meristic characteristics, otolith morphology, and DNA techniques. The resultsconfirmed the existence of six distinct species including Hemiramphus far, Hemiramphus lutkei, Hemiramphusarchipelagicus, Hyporhamphus limbatus, Rhynchorhamhus naga and Rhynchorhamphus georgii belonging tofamily Hemiramphidae, in Indian waters. In addition, DNA barcodes were generated for all theaforementioned species. These genetic sequences have been deposited in the Gene Bank, specifically in theBOLD Systems database. Notably, the study has generated barcodes by using COI gene for Hemiramphusarchipelagicus and Hemiramphus lutkei for the first time.